STUDY OF ANGINA PECTORIS USING MEDICAL TECHNOLOGIES (International journal of artificial intelligence, 2025)
Angina pectoris is one of the most common forms of coronary artery disease, characterized by chest pain caused by insufficient blood supply to the myocardium. In recent years, the development of medical technologies has opened new possibilities for more accurate diagnosis and effective treatment of this condition. The use of artificial intelligence, biomedical sensors, and advanced imaging techniques has significantly enhanced the process of angina detection, allowing for earlier diagnosis and better prediction of disease progression. Artificial intelligence systems based on machine learning algorithms analyze data from ECG, echocardiography, coronary angiograms, and other sources, enabling the identification of changes in the early stages of the disease, when traditional diagnostic methods may be ineffective. The application of these technologies contributes to a more individualized approach to treatment and allows for better monitoring of therapy effectiveness, which, in turn, improves the prognosis for patients with angina. This study explores the application of medical technologies in angina diagnosis, their potential benefits, and the impact they have on treatment quality.